Dampak dan Evaluasi Penyelenggaraan Pemilihan Umum Serentak 2019 di Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Since 2004, Indonesians have been granted the opportunity to directly elect their president and vice president, leading to two rounds of elections to select legislative members, as well as the president. In 2019, the Indonesian government made a significant decision to conduct concurrent general elections for both legislative and presidential. This research adopts qualitative research methods and utilizes literature review as its data collection approach. The findings of this study reveal that the simultaneous holding of the 2019 General Election has yielded diverse impacts, primarily stemming from logistical challenges, duplicated data on the voters list, excessive information overload among the public leading to irrational voting decisions, and unfortunate casualties, including the loss of hundreds of election committee officers' lives. Consequently, it highlights the pressing need for the General Election Commission (KPU) to thoroughly evaluate and address these issues while organizing the 2024 elections simultaneously.